Interaction in the systems WC-Ni-Al and WC-NiTi in sintering and impregnation; Soviet Powder Metallurgy and Metal Ceramics; Vol. 25, iss. 5 - Kulkov S. N. Sergey Nikolaevich (1989, 1989)
The object of this work was to study the interaction of powder tungsten carbide with the alloy NiTi and Ni-Al in sintering and impregnation. Results of this study show that in consequence of the high activity of titanium in titanium nickelide there is intense interaction between tungsten carbide and the cementing bond, entailing the formation of the phases Bi2W3C, TiWC, which embrittle the material considerably. As far as the system WC-Ni-Al is concerned, compact material with retained initial phase structure can be obtained solely by the method of impregnation within a short time.